Electrochemical method for the determination of arsenic 'in the field' using screen-printed grid electrodes - Dudeney, Richard (Cranfield University, 2008)
This project describes development and problem solving efforts to realise a viable portable sensor for arsenic, applicable to drinking water. The work is the first dedicated effort towards this goal, after the preliminary investigations previously conducted at Cranfield University (Cooper, 2004 and Noh, 2005). Using polymeric gold ink BQ331 (DuPont Microcircuit Materials, Bristol, UK) as working electrode on screen printed strips, the electrochemical procedure was studied. Due to the wealth of research on electrochemical and non electrochemical methods for arsenic determination, this project attempts to capitalise on the unique advantages of the screen-printed gold surface. In particular, the issues surrounding the performance of the sensor were evaluated by electrochemical and spectroscopic means (including infrared, nuclear magnetic resonance and X-ray photoelectron spectroscopy). A number of custom screen printed electrodes were prepared in house comparing sensor performance on compositional factors. An interference coming from silver interaction with chloride in the reference electrode was identified. As such, the design of the sensor needs to change to include either an immobilising layer, such as Nafion, over the silver, or to omit screen-printed silver altogether. The Nafion was presumed to work by excluding (or at least much reducing) the passage of negatively charged chloride ions to the silver surface preventing formation of soluble silver chloride complexes. The design of the sensor was considered in light of performance and sensitivity. The screen-printed electrodes were cut to facilitate a microband design lending favourable diffusive to capacitive current characteristics. With this design, As(III) detection was demonstrated comfortably at 5 ppb (in a copper tolerant 4 M HCl electrolyte) without electrode need for additional preparation procedures. This is below the World Health Organisation (WHO) guideline and United States Environmental Protection Agency (USEPA) regulation level of 10 ppb in drinking water. The electrode materials are already mass manufacturable at an estimated cost less than £ 0.5 per electrode. Themicroband design could, in principle, be applied to mercury and other metal ions. The procedure for As(V) either with chemical or electrochemical reduction and determination still needs to be assessed. However, the presented electrode system offers a viable alternative to the colorimetric test kits presently employed around the world for arsenic in drinking water. Also, the Nicholson Method (Nicholson, 1965a), used for characterising electron transfer kinetics at electrode surfaces, was extended for application to rough surfaces using a fractal parameter introduced by Nyikos and Pajkossy (1988). This work includes mathematical derivation and numerical evaluation and gives a number of predictions for electrochemical behaviour. These predictions could not be tested experimentally, as yet, since the physical conditions must be carefully controlled.